Роль компьютерно-сетевой информации в жизни современного общества и человека - Карпенко, В. Е.; Киселёва, В. Ю. (НТУ "ХПИ", 2018)
Авторами анализируется степень проникновения компьютерно-сетевой информации в жизнь как отдельного человека, так и социума. Роль сетевых ресурсов с каждым годом становится все более значимой для успешной деятельности организаций и взаимодействия людей между собой. Всё новая сетевая информация совокупно с уже существующей амбивалентно влияет на человеческие решения.

The authors analyze the degree of penetration of computer-network information into the lives of both individuals and societies. The role of network resources year by year has been becoming more important for the successful operation of organizations and the interaction of people among themselves. All new network information together with the already existing ambivalently affects human decisions.
The role of computer-network information in the life of contemporary society and human beings
Keywords: интернет; новости вирусные; общество; человек; Internet; viral news; society; human